Programmatic evaluation of mass drug administration for elimination of lymphatic filariasis and reasons for non-compliance in Gulbarga district, Karnataka in 2015 - Naresh Kumar, S. J.; Sunil, B. N. (International Journal Of Community Medicine And Public Health, 2018)
Background: Mass drug administration (MDA) to eliminate lymphatic filariasis (LF) is conducted once annually in the identified endemic districts of the country. MDA implementation is assessed by appointed independent teams within 2-3 weeks of the activity to suggest mid-term corrections and strengthen the on-going programme. This study was undertaken to assess the process of MDA implementation, drug coverage and compliance and to identify the reasons for non-compliance. Methods: A survey of four clusters comprising of three rural and one urban area was conducted in Gulbarga, during the third week following the MDA campaign in the district. Information pertaining to the MDA beneficiaries of the 124 evaluated households was collected over a period of three days using a structured proforma. The process of MDA implementation was evaluated at the district, taluk and primary health centre (PHC) levels. Results: From the information collected on 673 inmates of the households surveyed, the coverage and compliance rates of 87.5 and 60.9% respectively was found for diethylcarbamazine citrate and albendazole distribution and consumption. The important reasons for non–compliance to swallow the drugs identified were the beneficiaries being out of station during the campaign, was not aware of it, the drug distributer did not visit the beneficiaries house and fear of side effects of the drugs. Conclusions: Efforts to improve the compliance to consumption of the anti-filarial drugs at Gulbarga district is required for elimination of LF.